2006
DOI: 10.1016/j.neuron.2006.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of a Microbial-Type Rhodopsin Restores Visual Responses in Mice with Photoreceptor Degeneration

Abstract: The death of photoreceptor cells caused by retinal degenerative diseases often results in a complete loss of retinal responses to light. We explore the feasibility of converting inner retinal neurons to photosensitive cells as a possible strategy for imparting light sensitivity to retinas lacking rods and cones. Using delivery by an adeno-associated viral vector, here, we show that long-term expression of a microbial-type rhodopsin, channelrhodopsin-2 (ChR2), can be achieved in rodent inner retinal neurons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
603
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 685 publications
(665 citation statements)
references
References 56 publications
22
603
1
9
Order By: Relevance
“…The study demonstrated ON responses in all recorded retinal ganglion cells and visually evoke potentials in the cortex. 23 Similar treatments were shown to evoke changes in behavior in rat models of RP. 43,44 Furthermore, blind transgenic mice 45 and rats 46 have been generated that express ChR2 only in a subset of ganglion cells.…”
Section: Strategies For Optogenetic Restoration Of Visionmentioning
confidence: 88%
See 2 more Smart Citations
“…The study demonstrated ON responses in all recorded retinal ganglion cells and visually evoke potentials in the cortex. 23 Similar treatments were shown to evoke changes in behavior in rat models of RP. 43,44 Furthermore, blind transgenic mice 45 and rats 46 have been generated that express ChR2 only in a subset of ganglion cells.…”
Section: Strategies For Optogenetic Restoration Of Visionmentioning
confidence: 88%
“…Patients who are legally blind are the key target population of these therapies. Three different strategies are being investigated: (1) the implantation of differentiated or undifferentiated photoreceptors, 19 (2) electronic retinal implants, [20][21][22] and (3) the subject of this review, so-called 'optogenetic' approaches, [23][24][25] which use genetically encoded light sensors to make cells light responsive. [26][27][28] The success of cellimplantation approaches depends on the formation of functional synapses between the implanted photoreceptors and endogenous bipolar cells, and on functional retinal pigment epithelium to supply photoreceptors with 11-cis-retinal.…”
Section: Potential Therapies For Retinitis Pigmentosamentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, these characteristics have also made the retina the quintessential model for the therapeutic potential of optogenetics. Several groups have shown that, following the loss of photoreceptors, light-sensitivity can be reintroduced into remaining retinal neurons using optogenetic techniques [7,8]. A similar approach could be applied to other retinal diseases, particularly those with known cell-based dysfunctions.…”
Section: Resultsmentioning
confidence: 99%
“…Optogenetics thus allows for the noninvasive activation or inhibition of specific cells with light, a method that can be leveraged to combat a wide range of neurological conditions. Already, the potential of optogenetic techniques has been demonstrated in sciatic nerve injury [2], Parkinson's disease [3], epilepsy [4], depression [5,6], and retinal degeneration [7,8]. In this work, we describe a new method of using optogenetic techniques to study retinal circuit interactions between neurons and vascular cells, and show how this general approach can be potentially applied to treat neurological diseases.…”
Section: Introductionmentioning
confidence: 99%